ANALISIS KESENJANGAN ANTARA CONFORMANCE DENGAN ACTUAL PERCEPTION JASA PERTAKSIAN DI DKI JAKARTA - Nidjat Ibrahim (Media Riset Bisnis & Manajemen, 2002)
This paper explores factors that infiuence the customersatisfaction in the service area. There are 5 dimentions service quality: tangible, reliability, responsiveness, assurance, and empa- thy. The objective of this research is to see the perceived value profile and conformance that related the 5 dimenstions of service quality above in measuring customer satisfaction for taxi service in DKI Jakarta. Based on the statistic examination the paper argues that the taxi service in DKI Jakarta has not satisfied yet. Beside that the paper argues that there are stronge enough gaps between confomance andactual perception from the customerpercep- tive.